Membrane anchoring stabilizes and favors secretion of New Delhi metallo-β-lactamase - Gonzalez, Lisandro Javier (2016)
Carbapenems, 'last-resort' β-lactam antibiotics, are inactivated by zinc-dependent metallo-β-lactamases (MBLs). The host innate immune response withholds nutrient metal ions from microbial pathogens by releasing metal-chelating proteins such as calprotectin. We show that metal sequestration is detrimental for the accumulation of MBLs in the bacterial periplasm, because those enzymes are readily degraded in their nonmetallated form. However, the New Delhi metallo-β-lactamase (NDM-1) can persist under conditions of metal depletion. NDM-1 is a lipidated protein that anchors to the outer membrane of Gram-negative bacteria. Membrane anchoring contributes to the unusual stability of NDM-1 and favors secretion of this enzyme in outer-membrane vesicles (OMVs). OMVs containing NDM-1 can protect nearby populations of bacteria from otherwise lethal antibiotic levels, and OMVs from clinical pathogens expressing NDM-1 can carry this MBL and the blaNDM gene. We show that protein export into OMVs can be targeted, providing possibilities of new antibacterial therapeutic strategies.